New Lad: Re-Packaged Masculinity in Men’s Lifestyle Magazines - Singhakowinta, Jaray (NIDA Journal of Language and Communication, 2017)
This paper examines the representation of new lad in men’s lifestyle magazines and the cultivation of the masculine identity among magazine readers, seeking to understand how this construction of new lad affects the way the masculine gender is performed and conceptualised in a broader social context. Four focus group interview scripts of magazine readers, sponsored by the ESRC and conducted by ESRC researchers in 1997, are analysed by using the qualitative data analytical software, Nvivo, to provide a systematic understanding of the cultural shift in the construction of masculinity and the proliferation of male consumerism, represented in men’s magazines. This paper argues that the displacement of softer new man identity and the eager embrace of new lad archetype by UK men’s lifestyle magazines is a reassertion of masculine power in a subtler format.